Current status of solar-assisted greenhouse drying systems for drying industry (food materials and agricultural crops) - Ahmad Fudholi (Tanjung Malim, 2021)
Current status of solar-assisted greenhouse drying systems for drying industry (food materials and agricultural crops) by Ahmad Fudholi